MULTICULTURAL EDUCATION BASED ON SUNDA PHILOSOPHY IN THE KARATWAN GALUH PAKUAN CUSTOMARY INSTITUTION - Noviyanti Maulani; Tati Narawati; Yudi Sukmayadi (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
Multicultural education is a very important issue in Indonesia, which is a plural country. Sundanese philosophy is one of the cultural heritages that has the potential to support multicultural education. Karatwan Galuh Pakuan is an Indigenous Institution in Indonesia that applies multicultural education based on Sundanese philosophy.  The purpose of this study is to analyze how the multicultural concept based on Sundanese philosophy and how LAK Galuh Pakuan integrates the values of Sundanese cultural philosophy side by side with other cultures.  This research was conducted through a qualitative approach with a research design using exploratory type case studies. The location chosen to be a partner in this research is the Karatwan Galuh Pakuan Subang Traditional Institute. To obtain rich and authentic data, it is necessary to do interviewing techniques, observation, literature studies, and documentation.   The findings of this study that the Karatwan Galuh Pakuan Customary Institution is one of the representative forums of all multicultural education sectors that are sustainable from year to year (consistent) and are seen as activities as unifying the nation through the basics of Sundanese philosophical values that can foster community appreciation of diversity.